PROGRAM BIMBINGAN IMAN KEPADA TAKDIR BAGI DEWASA AKHIR PASCA PENSIUN - Akhmad Alim; Desi Permata Sari; Imas Kania Rahman (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The main problem that occurs in this study is the lack of knowledge in late adulthood to face retirement, with the lack of sipiritual will make the final adult unprepared to continue life and make depression due to reduced activities that previously worked actively and became alone at home without activity. The purpose of this study is to analyze the concept of faith in destiny by Muhammad bin Ibrahim Al-Hamd and analyze the training program for retirement preparation at ESQ MPP Indonesia. The method used in this study uses a qualitative approach with a library research and field research approach. with data collection using interviews, observations and documentation. Data analysis techniques use miles and huberman analysis. With the results of the analysis of the concept of faith in destiny according to Muhammad bin Ibrahim Al-Hamd that faith in a truly perfect destiny will lead a person to improve his every worship, and is also reflected in noble morals. Faith in destiny in everyone will also bear fruit such as gratitude, patience, sincerity, ridha, steadfastness, qana'ah. Analysis of the ESQ MPP Indonesia retirement preparation training program that retirement is a time that really needs a program in the form of guidance and training because at this time each individual will feel excessive anxiety and fear with the developmental tasks he must achieve. And the faith guidance program for destiny for late post-retirement adults provides programs to everyone who enters retirement, including operational services and responsive services, with training programs, seminars and workshops that can support when entering retirement.